Acute Effect of Four Stretching Protocols on Change of Direction in U-17 Male Soccer Players - Mohamed Amine Ltifi; Mohamed Chedly Jlid; Jérémy Coquart; Nicola Maffulli; Roland van den Tillaar; Ridha Aouadi (Sports, 2023)
Background: The ability to rapidly change direction while sprinting is a desirable athletic skill in soccer. Enhancing change of direction (COD) performance depends almost exclusively on specific training, with stretching traditionally considered one such intervention. However, the comparative impact of diverse stretching methods on COD in soccer players remains an area of interest. Therefore, this study aimed to compare the effects of different stretching methods on COD ability in soccer players. Methods: Twelve male soccer players playing in the national championship football division II (age: 16.3 ± 0.3 years, height: 1.81 ± 0.10 m, body mass: 67.7 ± 7.2 kg) were tested for COD performance (i.e., Illinois agility test) after (1) control condition (20 min general warm-up without stretching), (2) static stretching, (3) dynamic stretching, (4) combined static-dynamic stretching, and (5) combined dynamic-static stretching. The duration of stretching intervention was approximately 6 min for static and dynamic stretching and 12 min for both the combined stretching conditions. The experimental sessions were separated by 72 h. Results: COD improved after dynamic stretching when compared to any other condition (p: 0.03–0.002; ηp2: 0.56–0.73), except for the control condition (p = 0.146; ηp2 = 0.18). In contrast, static stretching induced a detrimental effect on COD when compared only to the dynamic stretching condition (p < 0.01; ES = 1.35). Conclusion: Dynamic stretching exercises used by male soccer players in the warm-up improved COD. Other forms of stretching exercises, particularly static stretching, negatively impacted the COD performance. Therefore, coaches can consider integrating dynamic stretching protocols tailored to the athletes’ specific needs. Moreover, extending the investigation to encompass a wider range of athletes, including different age groups and genders, would enhance the applicability and generalization of the findings.